Application and Characterization of Surfactants 2017
DOI: 10.5772/intechopen.68184
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Application of Selected Fungi Strains in Removal of Commercial Detergents and Biotechnology

Abstract: The consumption of synthetic detergents is increasing year by year due to increasing urbanization, which reflects on higher concentration of this pollutant in the environment. In order to purify wastewaters from different pollutants, the application of new technologies such as bioremediation is necessary. From the environmental point of view, it is important to identify microorganisms that are tolerant to the presence of this pollutant. This chapter presents the experimental evaluation of ability of several fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…1 e, f). In line with our results, Jakovljević and Vrvić ( 2017 ) suggested that genus Mucor were cotton candy colonies that grow rapidly at 25–30 °C, dark grayish-brown or light olive-gray aerial mycelium when grown on typical laboratory media.
Fig.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…1 e, f). In line with our results, Jakovljević and Vrvić ( 2017 ) suggested that genus Mucor were cotton candy colonies that grow rapidly at 25–30 °C, dark grayish-brown or light olive-gray aerial mycelium when grown on typical laboratory media.
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…NRCC6 dead biomass showed the highest removal efficiency (RE) toward Pb 2+ and Zn 2+ (100%) ˃ Ni 2+ (97.39%) ˃ Mn 2+ (88.70%) ˃ Cd 2+ (78.95%) ˃ Cu 2+ (74.00%) ˃ Fe 3+ (70.22%) ˃ As 2+ (68.57%) ˃ Cr 6+ (60.00%) from industrial wastewater (Table 6 ). The perspective of filamentous fungi in removing of commercial detergent has been continuously described over the past three decades from the species of Aspergillus , Penicillium , Rhizopus , Mucor , Humicola , Thermoascus , and Thermomyces (Jakovljević and Vrvić 2017 ). In accordance with our results, Sharma et al ( 2022 ) stated that using fungi including P. chrysosporium , Phlebia brevispora , and Phlebia floridensis is a new efficient and eco-friendly method that revealed a maximum removal of 98–99% for Ni, 97–98% for Cd, and 12–98% for Pb from the industrial wastewater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the fungal dry biomass of the culture broth, post-biodegradation, was measured at the end of the 30-day incubation period [ 49 ]. The biomass was filtered by a grade 4 Whatman filter paper (Merck & Co., Inc., Kenilworth, NJ, USA), washed with chloroform, then dried at 60 °C for 24 h. After cooling, the amount of dried biomass was measured by a high precision analytical scale (Thermo Fisher Scientific, Waltham, MS, USA).…”
Section: Methodsmentioning
confidence: 99%